2002
DOI: 10.1007/s00442-002-0909-5
|View full text |Cite
|
Sign up to set email alerts
|

Does competition magnify the fitness costs of induced responses in Arabidopsis thaliana? A manipulative approach

Abstract: Studies have increasingly shown that the constitutive or induced expression of resistance in plants is costly to fitness in the absence of enemy attack. If such costs are based on resource allocation tradeoffs, it has been hypothesized that resource limitation associated with plant competition increases the fitness costs of resistance. In two greenhouse studies, I examined the expression and costs of induced responses in pot-grown Arabidopsis thaliana grown alone or surrounded by six intraspecific neighbors. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
91
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 47 publications
3
91
0
3
Order By: Relevance
“…In wheat, Heil et al (6) demonstrated costs of SA-inducible defenses on growth and seed set. In Arabidopsis, Cipollini (7) showed that exogenously applied SA reduced seed production. Recently, Heidel et al (8) performed a field experiment with two sets of Arabidopsis genotypes: one group that is blocked in SA-inducible defenses and another group that constitutively expresses SA-inducible defenses.…”
mentioning
confidence: 99%
“…In wheat, Heil et al (6) demonstrated costs of SA-inducible defenses on growth and seed set. In Arabidopsis, Cipollini (7) showed that exogenously applied SA reduced seed production. Recently, Heidel et al (8) performed a field experiment with two sets of Arabidopsis genotypes: one group that is blocked in SA-inducible defenses and another group that constitutively expresses SA-inducible defenses.…”
mentioning
confidence: 99%
“…This cost-benefit paradigm has motivated most of the theory about the evolution of plant defenses against herbivores (5)(6)(7)(8). Conclusive evidence attributing fitness costs to a particular defense trait has been elusive, but recent studies have made significant advances (9,10). The paradigm has been difficult to test for two reasons: (i) fitness costs, which can be measured as reductions in either male (11) or female (1,9,12) reproductive function, arise from many different types of compromises that could result from the expression of defense traits; and (ii) the fitness costs of a defense trait must be disentangled from the costs of genetically correlated traits (13)(14)(15).…”
mentioning
confidence: 99%
“…2 and 3) have exploited inducible expression as a means of controlling for, or homogenizing, the genetic background of plants and have measured plant fitness before and after eliciting resistance in plants in herbivore-free environments. The discovery that herbivore attack elicits the JA cascade in many species, and that exogenous JA treatments elicits induced resistance without the wounding that normally accompanies herbivore attack, has motivated studies to measure the fitness costs of JA-induced responses (1,10,(26)(27)(28)(29). However, because of pleiotropic effects of the elicitors, the observed fitness differences do not arise solely from the expression of the resistant trait (12,30), and therefore these studies are likely to overestimate the fitness costs of resistance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Trade-offs between defense and growth and/or reproduction has been shown for quantitative defense traits such as protease inhibitors, which are considered costly chemicals to produce (Glawe et al, 2003;Zavala and Baldwin, 2006). Reallocation of resources from defense to growth may lead to better competitive ability (Cipollini and Bergelson, 2001;Cipollini, 2002;Moreno et al, 2009). Feng et al (2009 reported that the increased vigor of Ageratina adenophora, a neotropical invasive weed in Asia, is due to reallocation of nitrogen from cell walls (defense) to photosynthesis (growth), evidence that supports EICA.…”
Section: Eica Hypothesismentioning
confidence: 99%